Rating nurses' knowledge of basic steps of cardiopulmonary resuscitation - Joanna Stocka; Joanna Simińska; Weronika Bukowska; Piotr Porzych; Karol Ogurkowski; Krystyna Nowacka; Wojciech Hagner (Kazimierz Wielki University, 2018)
First aid is provided by the witnesses in this connection it is important to ensure that every citizen of the aid granted in a correct and effective until the arrival of emergency medical team. From witnesses to a large extent depend on the survival chances of the victim or his injury. Education in first aid begins in elementary school, however, important that the students of these classes were able to use the knowledge in practice